Bimbingan Teknis Tindak Lanjut Strategi Pengelolaan Keuangan Industri Kecil Kreatif pada LKP Mon N Me Kabupaten Bireuen - Jamaluddin; Rahmad; Zakaria Yahya; Taufik Jahidin; Adri Patria (LPPM Umuslim, 2022)
Basically, good financial management requires proper management and strategy. Financial management is related to good financial management, in order to be able to balance between income and expenses, to meet the needs of life and not get caught in financial difficulties. Financial ability is something that needs to be considered in today's modern life. Expertise in financial management is needed and carried out by business people, to manage their financial resources, with the ultimate goal of financial prosperity. This Technical Guidance (Bimtek) aims to provide financial management training so that it can be better understood and practiced for course participants and training at the Mom N Me Gandapura Course and Training Institute (LKP) Bireuen Regency. The results of the Bimtek have provided further understanding to all participants who took part in the training related to financial management strategies that are easier and more appropriate to plan and implement in their daily lives